Estudo sobre dietas à base de sorgo-soja, enriquecidas com caseína+lactose isoladas, destinadas a leitões desmamados - Leite, Silvana Cavalcante Bastos (2009)
The research was developed in the Division of Swine Pro duction, Department of Animal Science, Agricultural Science Center, Federal Un iversity of Ceará, with the objective of evaluating the animal performance, the occurrence diarrhea, the nitrogen metabolism indicators, animal well-being, and the production cost of piglets submitted to diets containing sorghum-soybean me al and isolated casein+lactose. The assay had the duration of 42 days and it was divided in two phases: 1 (21-42 days of age) and 2 (42-63 days of age ) during the nursery period. The experiment used a total of 40 piglets of a commercial line, weaned at 21 days of age (average weight of 4,76 kg). The exper iment followed a randomized blocks design, with 4 treatments, 5 repetitio ns and 2 animals per repetition, unfolded in a factorial 2 x 2 design, comp osed by two energetic feeds (corn and sorghum) and two milk products (dried skim milk a nd casein + lactose). Mean values were compared through the Duncan's tests 5 %. The diets were isoenergetics, isoproteics and isonutritives for lysine and methionine + cystine. In phase 1, a level of 21% crude protein (CP) and 3350 kcal ME was used and in phase 2, a level of 18,5 % crude protein (CP) and 32 50 kcal ME was used. The experimental diets were in number of 4 for phase: T 1 (corn+ dried skim milk), T 2 (corn + casein + lactose), T 3 (sorghum + dried skim milk) and T 4 (sorghum + casein + lactose). The use of sorghum and casein + lactose in weaned pig diets did not cause significant differences for nitrogen met abolism indicators, in both phases of assay. The treatments did not influence the w ell-being indicators. Related to animal performance and well-being no signi ficant interactions were registered (P>0,05) among the factors, during phases 1 a nd 2 of the nursery xxi period. The best economical answer for production of pi glets in the nursery period was obtained with the diet containing sorghum + casein + lactose (T4).